PERAN PARTAI ACEH UNTUK MEMBERIKAN PENDIDIKAN POLITIK KEPADA MASYARAKAT DI KOTA LANGSA - Mohammad Shadiqie Alfarizi; Harun H; Hamdani h (JURNAL ILMIAH MAHASISWA FAKULTAS HUKUM UNIVERSITAS MALIKUSSALEH, 2021)
This study aims to determine and analyze the role of the Aceh Party in providing political education to the people in Langsa City, the obstacles that make it difficult for the Aceh Party to provide political education and the efforts made by the Aceh Party to provide political education to all levels of society. Based on article 79(a) No. 11 of 2006 of the Law on the Government of Aceh states that local political parties function as a means of political education for members and the community. The Aceh Party in Langsa City has not been maximal in providing political education to all people in the Langsa City area. This can be seen from the lack of public understanding of political education as well as knowledge of the rights and obligations of the community in political education. This is because the Aceh Party in Langsa City still prioritizes political education for its cadres and the Aceh Party's "underbow". In addition, there is still a lack of public understanding of political education which is the responsibility of the Aceh Party, because the Aceh Party which won the general election in Langsa City must provide maximum understanding of political education to the community. This research method uses empirical juridical research methods with a library approach and field research. Literature research was conducted to obtain theoretical secondary data, while field research was conducted to obtain primary data through interviews with respondents and informants. Based on the results of the research that the role of the Aceh Party has not been maximal in providing political education to all people in the Langsa City area as mandated by the Political Party Law and UUPA. The obstacle for the Aceh Party in providing political education to the community is the lack of effectiveness of the Aceh Party in providing education and guidance to the entire community regarding the importance of political education in the nation and state. Efforts are being made to make the "Saweu Gampong" program and accommodate all the aspirations of the community so that the entire community can better understand political education with simplified delivery.